The many faces of autonomy: The normalised dynamics of claiming 'autonomy' through a creative policy game - Divald, S (2020)
Hungarian ethnic minority elites in Romania and Slovakia have vouched for autonomy arrangements as possible institutional solutions to deal with ethnic diversity. Yet, in the post-EU accession period, explicit claims to autonomy in Slovakia have essentially dropped off the radar of Hungarian minority elites since 2008. By contrast, most Hungarian political actors in Romania have had their own territorial autonomy plan since 2014. What accounts for these different trajectories of “autonomy” claims in Romania and Slovakia? The project uses elite interviews, party documents and newspaper archives in the original Hungarian language. It draws on qualitative text analysis to unpack how claims to autonomy unfold.